Syndemic burden and systemic inflammation, HIV health status, and blood pressure among women with unsuppressed HIV viral loads among women living with HIV. (1st November 2020) - Jones, Deborah L.; Rodriguez, Violeta J.; Alcaide, Maria Luisa; Carrico, Adam; Fischl, Margaret A.; Chichetto, Natalie E.; Rodriguez, Carlos J.; Welsch, Michael A.; Farah-Abraham, Rachael; Adimora, Adaora A.; D'Souza, Gypsyamber; Cohen, Mardge H.; et al.
Abstract : Introduction: Smoking, low education, obesity, and depressive symptoms are all associated with HIV health status, increased blood pressure, and inflammation, and constitute a syndemic burden that may contribute to poor health outcomes. The current study examined syndemic burden and health outcomes among women living with HIV. Methods: Women were participants enrolled in the Women's Interagency HIV Study. Outcomes included blood pressure, HIV health status (HIV-1 RNA viral load and CD4 + T-cell counts), and IL-6. Syndemic burden was defined as a count variable of low education, obesity, cigarette use, and depressive symptoms. Results: Women ( N = 131) were an average of 60.54 years of age (SD = 8.86), and 49% were non-Hispanic Black. In multivariable analyses, syndemic burden was not significantly associated with SBP ( P = 0.342) or DBP ( P = 0.763), IL-6 ( P = 0.168), or CD4 + cell count ( P = 0.846). However, syndemic burden was associated with increased viral load (age adjusted β = 0.35, P < 0.001). Comparing women with high versus low syndemic burden, also controlling for women's age, women with high syndemic burden had higher DBP and HIV viral load. Discussion: Syndemic burden appeared to play an important role in HIV health status and could potentially increase the risk of HIV transmission. High syndemic burden, defined as at least two syndemic conditions, had the greatest effects of HIV viral load and DBP. Targeted interventions to address syndemic burden may help improve health outcomes in women living with HIV as well as reduce the risk of hypertension and HIV transmission.